Evaluation of curcumin-based ophthalmic nano-emulsion on atropine-induced dry eye in mice - Mahsa Hadipour Jahromy; Mahnaz Qomi; Simin Fazelipour; Nafiseh Sami; Farzaneh Faali; Mehrnaz Karimi; Farhad Adhami Moghadam (Heliyon, 2024)
Background: One of the most efficient treatments for dry eye syndrome (DES) is to use nanocarriers as a potential delivery system. We aim to evaluate curcumin in a nano emulsion formulation. Methods: A new formulation containing 5.5% curcuminoid was used. DLS, Zeta potential, TEM, and HPLC tests were performed to determine the size and morphology. First, 30 mice were selected as atropine-induced dry eye models. Next, 25 mice in 5 groups were treated with the nano emulsion at different doses, and corneal tissues were separated for evaluation. Results: The DLS test results were indicative of the particles' stability. Nano curcumin appeared to be thoroughly effective in all groups, with the highest dose showing the most similarity to the healthy control group. Conclusions: Curcumin-based nano emulsion eye drop is a promising candidate for DES management. However, further investigation is required to evaluate the possible risks in humans.